When DNA Is and Isn’t Magic: A Conjunctive Analysis of How Context Matters in Homicide Investigations - Chamberlain, Jillian L. (Homicide studies, 2025)
Previous studies of homicide have examined the probative value of DNA and other forensic evidence for increasing case solvability and identifying best practices in prioritizing investigative resources. The current study was designed to extend this research by evaluating how different types of model specifications may dramatically alter substantive conclusions about the overall and context-specific effects of a DNA match on the likelihood of a homicide’s solvability. Analyses of a sample of 315 homicide cases from Cleveland, Ohio revealed that the presence of a DNA match had no overall significant effect on case clearance, but the impact of DNA exhibited large context-specific effects on this case outcome when its effect was evaluated conjunctively within subsets of offense attributes (i.e., different case profiles involving the presence or absence of eyewitnesses, contact weapons, and incidents in indoor locations) and victim characteristics (i.e., gender, race/ethnicity, income level of the victim’s place of residency). Results show that the most difficult to solve homicide cases are assisted by DNA matches, while DNA matches in homicides that occurred indoors with no eyewitnesses were associated with lower solvability. The results of these analyses are discussed in terms of their implications for future research to better identify the particular situational contexts in which DNA evidence is most and least effective in homicide solvability.